Media Pembelajaran 35 Sirah Shahabiyah Berbasis Android - Wiyanto Wiyanto (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The rapid development in the telecommunications and digital world today makes android-based mobile devices basic needs for many people. The devices have even provided various kinds of learning media for the community. Further, even though the devices are easily to apply as learning media, they have not been a priority for Muslims in improving their knowledge, such as Sirah Shahabiyah (the journey of a female companion of the Prophet Muhammad). Due to the community’s little interests in learning Sirah Shahabiyah, it is necessary to create a learning application that allows the user and the community to easily learn it. The methods used to collect the data of this research are field study, literature review and previous literature review. The system is developed using a prototype system development method consisting of the stages of planning, analysis, design and implementation and is designed using Unified Modeling Language (UML). The result of this research is a learning application in the form of android-based Sirah Shahabiyah, by which the user and the community can easily learn Sirah Sahabiyah, facilitating pleasant and effective learning activities.